The Role of Artificial Intelligence in the Implementation of Alternative Dispute Resolution Mechanisms - Ottó, Illés (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
Alternative dispute resolution (ADR) has been gaining increasing importance in the management of legal conflicts, offering faster, more cost-effective, and cooperation-oriented solutions compared to traditional litigation. The emergence of artificial intelligence (AI) opens new perspectives in this field, particularly in mediation, where digital technologies can support both parties and mediators. This study demonstrates how AI can enhance the efficiency of mediation procedures: from processing and analysing large volumes of data, through providing information and decision support to the parties, to assisting and preparing mediators in their work. The research explores opportunities where AI, through interactive tools such as chatbots, simulations, or speech recognition systems, can improve transparency and build trust among parties, while also pointing out limitations and risks, especially in the areas of data protection, liability, and social acceptance. The paper argues that the relationship between mediation and AI is not merely a matter of technological innovation, but a systemic developmental direction that—if embedded in adequate regulatory and institutional frameworks—may contribute to the modernisation of the dispute resolution culture and its broader dissemination.